Development of Flipbook-Based Modules on Animal Life Cycle Material for 4th Grade Students of Besowo 4 Elementary School - Fara Nurhaliza; Muhamad Basori; Sutrisno Sahari (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the results of observations that have been made in class IV SDN Besowo 4 Kediri Regency. The lack of variation in teaching animal life cycle material to 4th grade students. This can make students quickly bored and less interested in learning the learning material. The purpose of the study was to determine the validity, practicality, and effectiveness of the flipbook-based module on animal life cycle material. In this study using the ADDIE development model which includes five stages, namely: Analysis Stage, Design Stage, Development Stage, Implementation Stage, Evaluation Stage. The conclusion of the research results of the flipbook-based module on animal life cycle material for 4th grade students of SDN Besowo 4 Kediri Regency was declared very valid through the validation stage carried out by the flipbook-based module validation of 93% and from the material validation obtained a percentage of 86% which was declared very valid and very usable. To find out the effectiveness of the flipbook-based module can be seen from the results of the evaluation questions, the average value of the evaluation questions in the broad trial of 90% has exceeded the predetermined KKM. Thus, it can be concluded that flipbook-based modules are effectively used in learning.